2004
DOI: 10.1016/j.bcp.2004.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytamoxifen protects against oxidative stress in brain mitochondria

Abstract: This study evaluated the effect of hydroxytamoxifen, the major active metabolite of tamoxifen (synthetic, nonsteroidal antiestrogen drug), on the function of brain mitochondria. We observed that only high concentrations of hydroxytamoxifen (60 nmol/mg protein) induced a significant decrease in RCR, while ADP/O ratio remained statistically unchanged. Similarly, only the highest concentration of hydroxytamoxifen (60 nmol/mg protein) affected the phosphorylative capacity of brain mitochondria, characterized by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Previously, Zhou et al [35] showed that the decrease in Ca 2+ loading capacity promoted by DOX treatment is not reversed over a 5-week period after the discontinuation of the treatment, suggesting that the alteration of mitochondrial Ca 2+ regulation induced by DOX is persistent and irreversible. In accordance with previous studies, preincubation of mitochondria with oligomycin plus ADP or CsA, the inhibitors of PTP, significantly increased the capacity of mitochondria to accumulate Ca 2+ [6,[39][40][41]. It is known that the PTP is potentiated upon the oxidation of protein thiol groups in the pore complex [42].…”
Section: Discussionsupporting
confidence: 89%
“…Previously, Zhou et al [35] showed that the decrease in Ca 2+ loading capacity promoted by DOX treatment is not reversed over a 5-week period after the discontinuation of the treatment, suggesting that the alteration of mitochondrial Ca 2+ regulation induced by DOX is persistent and irreversible. In accordance with previous studies, preincubation of mitochondria with oligomycin plus ADP or CsA, the inhibitors of PTP, significantly increased the capacity of mitochondria to accumulate Ca 2+ [6,[39][40][41]. It is known that the PTP is potentiated upon the oxidation of protein thiol groups in the pore complex [42].…”
Section: Discussionsupporting
confidence: 89%
“…2 and 3). Accordingly, previous in vitro studies also indicate that TAM (Custodio et al, 1998;Moreira et al, 2005) and OHTAM (Cardoso et al, 2002;Moreira et al, 2004) are potent inhibitors of PTP induction in liver and brain mitochondria. However, we observed that E2 exposure does not interfere with Ca 2+ influx (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, changes in the structural and functional characteristics of mitochondria provide a number of primary targets for drugs-induced toxicity and cell death (Wallace and Starkov, 2000). Indeed, accumulating evidence indicates that both 17β-estradiol (E2) (Zheng and Ramirez, 1999;Yang et al, 2004) and TAM (Custodio et al, 1998;Moreira et al, 2004Moreira et al, ,2005) modulate mitochondrial function.…”
Section: Introductionmentioning
confidence: 99%
“…Tamoxifen, or its immediate metabolite 4-hydroxytamoxifen, are effective antioxidants (Dubey et al, 1999;Wiseman et al, 1994), and antioxidants have been clearly shown to be protective in brain trauma and stroke (Hall et al, 1989;Chan, 1999). The major tamoxifen metabolite, 4-OH tamoxifen was shown to markedly reduce induced lipid peroxidation in brain mitochondria in vitro (Moreira et al, 2004), but the antioxidative effects of tamoxifen have never been directly tested in stroke models. During ischemia and especially during reperfusion there are high levels of free radicals generated, which would be expected to attack proteins and lipids of the cell membrane and mitochondria.…”
Section: Antioxidant Activity and Tamoxifen-induced Neuroprotectionmentioning
confidence: 99%